APPLICATION OF ALL IN ONE SYSTEM METHOD IN ARABICLEARNING AT MI AL-FALAHIYAH MLANGI, NOGOTIRTOGAMPING SLEMAN YOGYAKARTA - Azizah, Malihatul (THORIQOTUNA: Jurnal Pendidikan Islam, 2018)
This study aimed to determine the application of the All In OneSystem Method in Arabic learning as well as supporting and inhibitingfactors in its implementation. This type of research was qualitativeresearch, with triangulation analysis using direct observation of theimplementation of the open interview observation method, anddocumentation. The results showed that Arabic learning at 3th grade atMI Al Falahayiah used the All In One System Method. This method is amethod in which the implementation consists of a system consisting offunctional elements that indicate an integrated sub-system that cannotbe separated (integral). All In One method is characterized byemphasizing the direct method. This means that educators directly useArabic as the language of instruction in teaching, educators areaccustomed to dialogue using Arabic. This method covers fourlanguage skills that are taught in a material, one title and one book, thefour language abilities are : sound, vocabulary, sentence structure andwriting that were applied directly